Apsara figure carved on the shaft of a pillar - Temples of India Project Team (Jio Institute, 2024)
Unlike other apsaras (celestial damsels) carved on the shaft of pillars, this particular figure is unique. She is crowned and holds a cup in her left hand, while her right hand holds something dipped in the cup. Similar images from the Harshnath Temple Complex depict a cup being held, symbolizing the nectar of bliss attained after the completion of tantric sadhana, while the fingers of the other hands are sometimes dipped into the cup. However, connecting this obscure image of a damsel with tantric connotations might lack substantial support.